2017
DOI: 10.1039/c7em00286f
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation and risk assessment of PM2.5 and PM2.5–10 in the ambient air of Kenitra, Morocco

Abstract: The seasonal and spatial variations of particulate matter (PM2.5-10 and PM2.5) and its chemical composition have been studied over a one-year period in Kenitra city (2007-2008). The samples were collected using Gent stacked filters and dichotomous samplers in two size fractions: below 2.5 μm (fine) and 2.5 to 10 μm (coarse). The chemical compositions of the collected filters were evaluated by using Total X-ray Fluorescence and Atomic Absorption Spectroscopy. The influence of atmospheric transport scenarios on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…A single backward trajectory has limited significance (Stohl 1998 ); therefore, to overcome the limitations and errors, cluster analysis was applied, a multivariate statistical analysis technique (Sokolov et al 2016 ; Xin et al 2016 ; Tahri et al 2017 ) to decipher the most important transport patterns (clusters). A new backward trajectory (72 h) was started every 6 h resulting in a total of 1460 trajectories, using the stand-alone version of the HYSPLIT.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A single backward trajectory has limited significance (Stohl 1998 ); therefore, to overcome the limitations and errors, cluster analysis was applied, a multivariate statistical analysis technique (Sokolov et al 2016 ; Xin et al 2016 ; Tahri et al 2017 ) to decipher the most important transport patterns (clusters). A new backward trajectory (72 h) was started every 6 h resulting in a total of 1460 trajectories, using the stand-alone version of the HYSPLIT.…”
Section: Methodsmentioning
confidence: 99%
“…Transport pathways of air masses and the potential source areas can be identified using back-trajectory analysis (e.g., clustering trajectories) (Draxler and Rolph 2014;Stein et al 2015) and concentration-weighted trajectory (CWT) (Carslaw 2015(Carslaw , 2018 simulations. For example, back-trajectory analysis approaches were applied in different studies to analyze the long-range transport impact on air pollution (Jeong et al 2011;Makra et al 2013;Tahri et al 2017). Moreover, potential source contribution function (PSCF) and CWT methods can be successfully implemented to investigate the origins of pollutants (source areas) (Cheng et al 2013;Hao et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Crustal and marine enrichment factors (CEFs and MEFs, respectively) were calculated as explained in [8], using Al and Na as reference elements [25,26]. The upper crust concentration reported by Wedepohl [27] and the average sea composition reported by Goldberg [28] were used for the purpose.…”
Section: Discussionmentioning
confidence: 99%
“…For trying to obtain a first subdivision of elements according to their sources, CEFs and MEFs were used. In this way, it was possible to identify elements prevalently having crustal (CEF < 10, MEF > 10), marine (MEF < 10, CEF > 10) or anthropogenic (CEF > 10, MEF > 10) origin [26,34,35]. The box plots of calculated CEFs and MEFs for all PM 10 samples collected in 2015 are shown in Figure 1.…”
Section: Direct Digestion Of Pm 10 Samplesmentioning
confidence: 99%
“…One study demonstrated the potential of using polyacrylonitrile transparent materials associated with windows to increase filtration efficiency for particulate matter, including PM2.5 (Liu et al, 2015). Despite these precautions, inhalation of PM2.5 is often unavoidable, particularly during cold, seasonal weather (Hu et al, 2017; Tahri et al, 2017). If the PM2.5 is inhaled, there is the potential for injury to the lung cells, and possibly the associated capillaries (Xu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%